Tourist experience: Contemporary perspectives. Sharpley, R. & Stone, P. (Eds.). Oxon, UK: Routledge (2011) - Agapito, Dora (2014)
The consumption of experiences has been acknowledged as a key research topic in tourism studies, since everything in a destination can be experienced by tourists, whether it be places, people, or activities.